The Relationship between Punctuation Marks and Diacritical Marks: A Critical Study of the Most Prominent Calls for Reconsidering Punctuation and Introducing New Marks - rabouzi, samir (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract: Since punctuation marks were used in Arabic writing at the turn of the last century, libraries continue to receive increasingly researchers' studies carried out on this topic. Each praises their use, stresses the need to give importance to them, and sheds light on a painful reality that Arabic writing is going through in most of its forms and domains, until reaching an alarming point. In fact, calls to reconsider Arabic punctuation marks and to introduce additional signs that contribute to facilitate the understanding of written texts and remove ambiguities from them are increasing. It is regrettable that this intense attention to punctuation marks is at the expense of the status of the diacritical marks, and without taking into account the methodology of the ancient Arabs in writing Arabic texts and checking their correctness. In this paper, we will try to examine the history of diacritics and punctuation marks in Arabic, and define the relationship between them in order to discuss in light of this, these calls and review the evidence of their proponents.